PERJANJIAN KREDIT KENDARAAN BERMOTOR DENGAN FASILITAS PEMBIAYAAN MULTIGUNA TERHADAP ASAS KEBEBASAN BERKONTRAK - Muhamad Zanuar Zanuar Prasetyo; Cipto Kuncoro; Siti Afiyah (MIMBAR YUSTITIA, 2020)
BCA Multifinance provides consumer financing facilities (multipurpose financing) in the form of funding for the purchase of motor vehicles. Motor vehicle loan agreement with installment payments at PT. BCA Multifinance is carried out in writing in a standardized form. For this reason, it is necessary to research whether the motor vehicle loan agreement with multipurpose financing facilities between the financing company and the customer (consumer) does not conflict with the principle of freedom of contract. The research method used is a normative legal research method. The use of this normative legal research method is based on the consideration that the discussion of the issues raised is related to the legislation, namely the Civil Code, and legal documents that have relevance to the goods credit agreement with the multipurpose financing facility of PT. BCA Multifinance Lamongan. Motor vehicle loan agreement with multipurpose financing facility based on the principle of freedom of contract, everyone may make a contract that contains and of any kind. Likewise, the existence of a standard clause in a motor vehicle loan agreement must meet certain conditions, both general requirements and special conditions so that the contract is valid according to law.